2020
DOI: 10.1002/ptr.6853
|View full text |Cite
|
Sign up to set email alerts
|

The safety and efficacy of Momordica charantia L. in animal models of type 2 diabetes mellitus: A systematic review and meta‐analysis

Abstract: Type 2 diabetes mellitus is a chronic hyperglycemic condition due to progressively impaired glucose regulation. Momordica charantia L. could potentially improve hyperglycemia because its fruit extracts can alleviate insulin resistance, beta‐cell dysfunction, and increase serum insulin level. We evaluated the effect of M. charantia L. in comparison with a vehicle on glycemic control in animal models of type 2 diabetes mellitus. MEDLINE, Web of Science, Scopus, and CINAHL databases were searched without language… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 82 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…[9][10][11] A systematic review and meta-analysis of M. charantia in animal models of type 2 diabetes showed that M. charantia reduces fasting plasma glucose and glycated hemoglobin A1c (HbA1c) levels, and dis-plays hepato-renal protective effects. 7 Clinical trials also showed that administration of M. charantia decreases the average fasting blood glucose and HbA1c levels, and increases the glucose clearance in patients with type 2 diabetes or prediabetes. 12,13 These findings indicate that M. charantia exhibits beneficial effects on the management of diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] A systematic review and meta-analysis of M. charantia in animal models of type 2 diabetes showed that M. charantia reduces fasting plasma glucose and glycated hemoglobin A1c (HbA1c) levels, and dis-plays hepato-renal protective effects. 7 Clinical trials also showed that administration of M. charantia decreases the average fasting blood glucose and HbA1c levels, and increases the glucose clearance in patients with type 2 diabetes or prediabetes. 12,13 These findings indicate that M. charantia exhibits beneficial effects on the management of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…6 Momordica charantia (bitter melon) is a common vegetable that has been applied in folk medicine for the management of blood glucose. 7,8 It exhibits various pharmacological functions, such as anti-hyperglycemic, antidiabetic, hepatoprotective, and anti-inflammatory activities. [9][10][11] A systematic review and meta-analysis of M. charantia in animal models of type 2 diabetes showed that M. charantia reduces fasting plasma glucose and glycated hemoglobin A1c (HbA1c) levels, and dis-plays hepato-renal protective effects.…”
Section: Introductionmentioning
confidence: 99%
“…The independent factors were concentrations of M. charantia fruit extract (MCFE) and A. esculentus fruit extract (AEFE), while the dependent factor was fasting plasma glucose levels (mmol/L). The minimum and maximum doses for MCFE (100-250 mg/kg) were determined based on previous studies [13], while previous optimization experiments determined the dose range of AEFE at 100-250 mg/kg [44]. The experiments were grouped in one block with the factorial and axial points that run one replicate at the center.…”
Section: Dose Of a Binary Mixture Of A Esculentus And M Charantia For...mentioning
confidence: 99%
“…Momordica charantia L. (Cucurbitaceae) is a popular vegetable in African countries, India, and China [10][11][12]. Pre-clinical studies showed that M. charantia preparations lower elevated blood glucose levels [13]. This action occurs through several mechanisms, including β-cell regeneration [14][15][16], insulin secretagogue [17,18], enhancing peripheral glucose utilization, inhibiting glucose-6-phosphatase and fructose biphosphatase glucogenic enzymes [19], increasing adiponectin release [20], and inhibit 11β-Hydroxysteroid dehydrogenase type 1 among other [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The bitter gourd extracts were evaluated for numerous pharmacological activities, and most of them were performed on animals. Fruits and seed extracts reduced fasting glucose and glycosylated hemoglobin A1c in comparison to vehicle control when tested in animal models of type 2 diabetes ( 24 ). The water extract of leaves proved to have an anti-obesity effect on a high-fat diet (HFD)-induced obese mouse model through regulating lipid metabolism ( 25 ).…”
Section: Introductionmentioning
confidence: 99%